Facility siting ‐ negotiating the minefield of "maximum credible event". Issue 4 (13th May 2021) - Graham, Kristen; Thomas, J. Kelly
Abstract: The purpose of this paper is to provide a case study that compares the results from a consequence‐based facility siting study (FSS) limited to a specified release size as the maximum credible event (MCE) versus a risk‐based study with a range of release sizes and associated frequencies. The results are intended to highlight potential differences in the building siting decisions made using a consequence‐based approach with a limited MCE versus those made with a risk‐based approach. Most recommended practices and other FSS guidance documents advise evaluating MCEs for an FSS. However, there can be uncertainty in MCE selection and the values used in industry span a considerable range. Arguments for limiting the MCE in a consequence‐based FSS to a 2‐in. release include that most accidental releases (i.e., > 95%) are smaller and that a 2‐in. release size is the largest that provides actionable information upon which siting decisions can be made. However, a number of well‐known incidents in industry involve releases larger than 2‐in., which introduces uncertainty as to a reasonable upper‐bound for an MCE. The use of a risk‐based FSS approach effectively eliminates the decision regarding release size since this approach aggregates the full range of operational scenarios and release sizes along with the associated likelihood of failure. Based on the MCE scenario(s) employed and the criteria selected, consequence‐based and risk‐based FSS evaluations for a given site may lead to very different conclusions as to which buildings are considered safe and what types of mitigation actions should be taken.